O estágio como espaçotempo de experiências na formação em educação física: diálogo com a Hermenêutica Gadameriana - Kleinubing, Neusa Dendena (2019)
This thesis treat to understand how the Philosophical Hermeneutics of Gadamer can be a perspective to think the learning to be professor of Physical Education in the experience of the stage. Organized as a theoretical study, the interpretations had as main source the work "Truth and Method I: Fundamental Traits of a Philosophical Hermeneutics", but other readings were necessary for the understanding of this theoretical-philosophical thought and other authors subsidized the reflections between the elements of hermeneutics and the formation of teachers. I start from the assumption that the stages in Physical Education constitute a space open to experience has as a background the aesthetic experience, being configured by the predisposition to listening and genuine dialogue with the other. The elements of philosophical hermeneutics as the happening of art, history and language are articulated throughout the thesis in order to emerge the arguments in defense of the idea presented. In this way, articulated to the concept of experience, we bring to the discussion the Bildung to which Gadamer presents his historical character of the formation that surpasses the mere cultivation of preexisting aptitudes for a certain end, contemplating the whole appropriation of what of and through which form. The thesis presents three interpretative horizons for the curricular stage: the first considers the relation between tradition, translation and composition in the search for new meanings for the formation as well as for the pedagogical performance of the Physical Education teacher; the second visualizes the stage as a space open to experience, showing that comprehension surpasses the logic of domination and control, embracing the recognition of the other as legitimate and indispensable, and the third discusses the stage as the possibility of the hermeneutic experience of self-formation, considering the encounter which is established between the student and the future field of action, participation in the production of meanings and Bildung as a perspective of formation in and by the stage. The contribution of this thesis is that it shows that Gadamer‟s hermeneutics is a prospect of great potential for thinking about the curricular stage in the formation of Physical Education teachers because, from the perspective of experience, the stage opens to new, to what is about to become the learning of being a teacher through listening, exchange and genuine dialogue. The restlessness arising from this posture raises new questions and with them, we continue to learn.